Repercussions of low fructose-drinking water in male rats - Miranda, Carolina Abreu; Schönholzer, Tatiele E.; Klöppel, Eduardo; Sinzato, Yuri K. [UNESP]; Volpato, Gustavo T. [UNESP]; Damasceno, Débora C. [UNESP]; Campos, Kleber E. (FapUNIFESP (SciELO), 2019)
Fructose consumption has increased worldwide, and it has been associated with the development of metabolic diseases such as insulin resistance (IR) and steatosis. The aim was to evaluate if lower fructose concentrations may cause pancreatic structural abnormalities, leading to a glucose intolerance without steatosis in male rats. Young male rats orally received 7% fructose solution for 12 weeks. Body weight, food, water, and energy intake were measured. An oral glucose tolerance test (OGTT) was performed. After final experimental period, all rats were anaesthetized and killed. Blood samples were collected for biochemical analyses and organs (liver and pancreas) were processed for morphological analyses. Fructose consumption was not associated with lipid accumulation in liver. However, fructose administration was associated with an increased area under curve from OGTT and an increased percentage of insulin-positive cells, high beta cell mass and reduced pancreatic islet area. Fructose supplementation (7%) did not cause steatosis, but it led to abnormal morphology and function of pancreatic islet cells, contributing for glucose intolerance development. Our findings demonstrate that even low fructose concentrations may cause deleterious effects in animals.
Keywords: Fructose; Glucose intolerance; Islet pancreatic; Steatosis